2023
DOI: 10.1021/acs.jpcc.3c00684
|View full text |Cite
|
Sign up to set email alerts
|

Betavoltaic Nuclear Battery: A Review of Recent Progress and Challenges as an Alternative Energy Source

Abstract: Nuclear energy is considered a suitable and eco-friendly alternative for combating the rising greenhouse gases in the atmosphere from excessive fossil fuel consumption. Betavoltaic battery is a form of nuclear technology that utilizes the decay energy of β-emitting radioisotopes to produce electrical power. Owing to its long shelf life, high specific energy density, and ability to work under extreme conditions, it has been a subject of considerable research attention in the past few years. Despite significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Intrinsic rather than doped silicon is chosen as the basis material of the battery in order to minimize the recombination losses. Indeed, it has been shown that the maximal limit efficiency of a silicon solar cell is achieved in the limit of zero doping [23], and same is true in the case of a betavoltaic cell [3]. In this idealized model, we assume that the T/Si layer is so thin that the self-absorption effect can be neglected.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrinsic rather than doped silicon is chosen as the basis material of the battery in order to minimize the recombination losses. Indeed, it has been shown that the maximal limit efficiency of a silicon solar cell is achieved in the limit of zero doping [23], and same is true in the case of a betavoltaic cell [3]. In this idealized model, we assume that the T/Si layer is so thin that the self-absorption effect can be neglected.…”
Section: The Modelmentioning
confidence: 99%
“…Here, E is measured in eV, F(E) in eV/Å, the distance s is measured along the velocity of the beta, Z = 14 and A = 28.085 are atomic charge and mass numbers, and ρ = 2.329 g/cm 3 is the density of Si, for which J = 172 eV, and k = 0.822. This formula becomes inaccurate at electron energies below 50 eV [34].…”
Section: Generation Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Yin and co-workers summarized the challenges and future directions for developing batteries that can perform and persist at extremely fast-charging (XFC) conditions . In a different approach to energy storage, the progress and challenges in the development of betavoltaic nuclear batteries was reviewed by Naseem et al Zhang and co-workers discussed the strategies involved in detecting and preventing the formation of gas hydrates in deepwater transportation of natural gas and oil. The challenges in this field are similar to those found in clathrate gas extraction and storage …”
mentioning
confidence: 99%